Social relationships in rehabilitation and their impact on positive outcomes among amputees with lower limb loss at Walter Reed National Military Medical Center - Seth Messinger; Sayeh Bozorghadad; Paul Pasquina (Medical Journals Sweden, 2017)
Objective: To explore how the social context of the clinic influenced the way former patients with lower limb loss in the Military Advanced Training Center at Walter Reed National Military Medical Center evaluated their outcomes. Design: Cross-sectional phenomenological-based interviews and observations. Patients: Twenty individuals with lower limb amputation were recruited from a multidisciplinary military treatment programme for patients with lower-extremity traumatic limb-loss injured in Afghanistan or Iraq. Methods: Lightly structured interviews were conducted either in person or over the telephone with former patients and clinical care-providers. Where possible, observation was conducted in conjunction with the interviews. The research team used content analysis of the data, consistent with ethnographic methods. Results: Analysis of the therapeutic effect of social relationships developed in the clinical rehabilitation programme identified 3 areas of significance: enduring relationships with key care-providers, access to treatment team by patients, and peer support among patients. Conclusion: The social component of service delivery influences patients' outcomes from clinical care. These results could be translated across healthcare settings to improve patient outcomes.